2019
DOI: 10.1016/j.cell.2019.01.025
|View full text |Cite
|
Sign up to set email alerts
|

Widespread and Functional RNA Circularization in Localized Prostate Cancer

Abstract: Highlights d Ultra-deep rRNA-depleted RNA sequencing of 144 localized prostate tumors d Fusion gene profiles differentiate localized from metastatic disease d Widespread RNA circularization events define clinically distinct tumor subtypes d Functional screening reveals pervasive circular isoformspecific essentiality

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

11
304
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 369 publications
(325 citation statements)
references
References 82 publications
11
304
3
Order By: Relevance
“…Their functions largely remain elusive, partly owing to the lack of effective tools to interfere with circular but not linear RNA levels in cells 1 . Short hairpin RNAs (shRNAs) or specific small interfering RNAs (siRNAs) targeting BSJ sites of circRNAs have been used to knock down circRNAs [3][4][5] . However, even partial complementarity of a half-RNAi (~10 nt) to linear mRNAs may affect parental gene expression (Extended Data Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Their functions largely remain elusive, partly owing to the lack of effective tools to interfere with circular but not linear RNA levels in cells 1 . Short hairpin RNAs (shRNAs) or specific small interfering RNAs (siRNAs) targeting BSJ sites of circRNAs have been used to knock down circRNAs [3][4][5] . However, even partial complementarity of a half-RNAi (~10 nt) to linear mRNAs may affect parental gene expression (Extended Data Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Twenty years later, the advent of high-throughput sequencing of non-polyadenylated transcriptomes and bioinformatic analyses have made it possible to detect thousands of circRNAs, many of which are highly abundant and conserved across species (3)(4)(5) . Accumulating evidence links circRNAs to development and progression of different diseases (reviewed in (6) ) and several recent studies have shown that circRNAs are involved in tumorigenesis (7,8) . Due to their structural stability (4) , tissue specificity (3) , and relatively high expression levels in exosomes (9) , blood (10) , and plasma (11) , circRNAs have been suggested as a new class of biomarkers and potential therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, shRNA-based functional screen has been employed to understand circRNA essentiality 1 . However, in our study, we observed frequent discrepancies between shRNAmediated circRNA knockdown efficiency and the corresponding biological effect on cell proliferation (see below), raising concerns about the robustness of using RNAi to study the function of circRNAs.…”
mentioning
confidence: 99%